Modelling uranyl chemistry in liquid ammonia from density functional theory. Issue 74 (30th August 2018) - Sieffert, Nicolas; Thakkar, Amol; Bühl, Michael
Abstract : We developed a computationally-efficient protocol based on Density Functional Theory (DFT) and a continuum solvation model (CSM) to predict reaction free energies of complexation reactions of uranyl in liquid ammonia. Abstract : We developed a computationally efficient protocol based on Density Functional Theory (DFT) and a continuum solvation model (CSM) to predict reaction free energies of complexation reactions of uranyl in liquid ammonia. Several functionals have been tested against CCSD(T) and different CSMs have been assessed relative to Car–Parrinello Molecular Dynamics (CPMD) simulations in explicit solvent.